Astragalus sinicus Incorporated as Green Manure for Weed Control in Corn - Liu, Silin; Ma, Zhiyi; Zhang, Ying; Chen, Zhongwen; Du, Xiao; Mu, Yinghui (Frontiers in Plant Science, 2022)
Astragalus sinicus L. (milk vetch), one of the most widespread green manure species, is widely planted in the temperate zone. Eleusine indica L. (goosegrass), a serious annual weed in the world, which has evolved resistance to some non-selective herbicides. The use of milk vetch as green manure for weed control in paddy fields was proposed. Aqueous extracts of milk vetch are known to exert a different level of phytotoxicity on weed and crops. Considering the need for searching new sustainable strategies for weed control, a question arises: ‘if milk vetch could be applied in goosegrass control, which stage is the most important to control goosegrass after milk vetch returned to the field, and at the same time, will the subsequent crop, corn (Zea mays L.), be affected by the side effects from milk vetch phytotoxicity?’ In this study, the potential of milk vetch for goosegrass control was approached by repeated laboratory experiments, which include the aqueous extract experiment, decomposed experiment and pot experiment. The effects of milk vetch returning to the field on maize were simulated by a pot experiment. The extract of milk vetch could significantly inhibit the germination of goosegrass at 2% concentration, and the inhibition enhanced with the increase of concentration. In the decomposed liquid experiment, decay time within 15 d, with the increase of decay d or concentration, goosegrass inhibition effect of decomposed liquid was enhanced. When decay time was more than 15 d, the inhibition ability of the decomposed liquid to goosegrass decreased. According to the RI accumulated value, aqueous extract and decomposed liquid have a “hormesis effect” on the germination and growth of goosegrass. Pot experiment proved that the addition of 1~10% (w/w) of milk vetch significantly reduced the germination and growth of goosegrass. On the contrary, the comprehensive analysis showed that the participation of milk vetch was conducive to the growth of corn. Our results constitute evidence that the incorporation of milk vetch into the soil could be a feasible practice to reduce weed infractions in the corn-based cropping system.